2018
DOI: 10.21037/jgo.2017.12.04
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy in ovarian and gastrointestinal peritoneal carcinomatosis: results from a 7-year experience

Abstract: A therapeutic approach that combined CRS + HIPEC could achieve long-term survival in selected groups of patients with PC from gastrointestinal, gynecological and others tumors with acceptable morbidity and mortality. A good expertise and a high volume of patients are necessary to manage PC and to further improve results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…34,[39][40][41][42][43]45,47,48,50,53 Many studies reported that additional procedures were needed to manage complications. 34,40,41,44,46,47,49,50,53,54 Given the risks associated with HIPEC, prospective studies have focused on using HIPEC immediately after debulking (as part of the same procedure) in patients with high-volume intraperitoneal disease (FIGO stage III-IV at diagnosis or recurrence), particularly those with peritoneal carcinomatosis, who are at risk for widespread residual microscopic disease even after resection to no visible disease. Compared with postoperative intraperitoneal therapy, intraoperative intraperitoneal administration may enable better perfusion of the peritoneal space because adhesions will not yet have formed.…”
Section: Hyperthermic Intraperitoneal Chemotherapy At the Time Of Idsmentioning
confidence: 99%
“…34,[39][40][41][42][43]45,47,48,50,53 Many studies reported that additional procedures were needed to manage complications. 34,40,41,44,46,47,49,50,53,54 Given the risks associated with HIPEC, prospective studies have focused on using HIPEC immediately after debulking (as part of the same procedure) in patients with high-volume intraperitoneal disease (FIGO stage III-IV at diagnosis or recurrence), particularly those with peritoneal carcinomatosis, who are at risk for widespread residual microscopic disease even after resection to no visible disease. Compared with postoperative intraperitoneal therapy, intraoperative intraperitoneal administration may enable better perfusion of the peritoneal space because adhesions will not yet have formed.…”
Section: Hyperthermic Intraperitoneal Chemotherapy At the Time Of Idsmentioning
confidence: 99%
“…However, the value of HIPEC in gastric cancer is controversial, It has reported CRS plus HIPEC yield fewer benefits in patients with PM from gastric cancer, and the median OS in GC is shorter than in other malignancies such as colorectal cancer, ovarian cancer, and appendicular cancer. [30,31] And clinical usefulness of systemic chemotherapy and HIPEC is judged to be moderate to high for PM of ovarian and colorectal origin but moderate to poor for gastric origin. [32] Contrast to these studies, the above studies mainly targeted the advanced gastric cancer with peritoneal metastasis, while, we aimed each stage of gastric cancer, and our IPHP procedure was not combined with chemotherapeutic agent, which may increase morbidity of adverse event.…”
Section: Discussionmentioning
confidence: 99%
“…The mainstay treatment for secondary peritoneal cancer is cytoreductive surgery (CRS) combined with hyperthermic intraperitoneal chemotherapy (HIPEC) [3][4][5][6]. Studies have revealed the improved survival rates of patients who received CRS + HIPEC treatment [7][8][9]. However, CRS + HIPEC treatment is a complex surgical procedure that commonly requires a long operation duration and causes significant surgical injuries.…”
Section: Introductionmentioning
confidence: 99%